Design and implementation of the AMIGA embedded system for data acquisition - Binet, V. (2021)
Fil: Fil: Binet, V. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Física de Rosario (IFIR-CONICET); Argentina